Sulphur Doped Graphitic Carbon Nitride as an Efficient Electrochemical Platform for the Detection of Acetaminophen. Issue 15 (1st January 2019) - Sakthivel, Arunkumar; Chandrasekaran, Anitha; Jayakumar, Shreenidhi; Manickam, Pandiaraj; Alwarappan, Subbiah
Abstract : Sulphur doped graphitic carbon nitride (S-g-C3 N4 ) is prepared by a one pot synthesis using thermal condensation of thiourea at 550°C. The as-synthesised S-g-C3 N4 is characterized by spectroscopic techniques such as UV-vis, FT-IR and Raman. Morphological and elemental analysis were performed using analytical techniques such as XRD, XPS, SEM, FESEM and TEM. Electrocatalytic activity of the S-g-C3 N4  was investigated towards the detection of acetaminophen in the presence of hydroquinone using cyclic voltammetry, differential pulse voltammetry and chronomamperometry. S-g-C3 N4  modified electrode exhibited an efficient electrochemical activity towards acetaminophen over two linear ranges: between 50 nm to 1.0 μM and 2.0 μM to 100.0 μM with sensitivity of 9.826, 2.154 μAcm −2  μM −1, respectively. The detection limit of S-g-C3 N4  modified electrode was calculated to be 25.84 nM (S/N = 3). The sensor exhibited excellent selectivity towards acetaminophen detection in the presence of interfering species such as hydroquinone, glucose, K +, Cl −, uric acid, citric acid and amoxicillin. Further, the level of acetaminophen in human serum samples were evaluated using the S-g-C3 N4  modified electrode. The results confirm the usefulness of the proposed sensing strategy for clinical applications.